Dark Web Investigation - Akhgar, Babak; Gercke, Marco; Vrochidis, Stefanos; Gibson, Helen (Security Informatics and Law Enforcement, 2021)
Intro -- Foreword -- Acknowledgements -- Contents -- Editor Biographies -- Contributors -- Part I: Foundations -- Chapter 1: Understanding the Dark Web -- 1.1 Introduction -- 1.2 Infrastructure of the Dark Web -- 1.2.1 The Tor Project (Tor): Overview -- 1.2.1.1 Search Engines and Introductory Points -- 1.2.2 Tor Architecture and Routing -- 1.2.2.1 Tor Nodes -- 1.2.2.2 Tor Directory Authorities -- 1.2.2.3 Tor Circuit -- 1.2.2.4 Setting Up Tor -- 1.2.3 The Invisible Internet Project (I2P): Overview -- 1.2.4 I2P Network Database -- 1.2.5 I2P Routers and Tunnels -- 1.2.6 Freenet: Overview -- 1.2.6.1 Freenet's Architecture and Design -- 1.2.6.2 Sharing, Requesting and Accessing Data -- 1.3 Law Enforcement Agency Investigating the Dark Web -- 1.3.1 How Policing the Clear Web Influences the Dark Web -- 1.3.2 The Dark Web Also Poses a "Policing Dilemma" -- 1.4 Concluding Remarks -- References -- Chapter 2: Using the Dark Web -- 2.1 Introduction -- 2.2 Dark Web Users -- 2.2.1 Non-criminal Actors -- 2.2.1.1 Public-Ordinary Users -- 2.2.1.2 Journalists -- 2.2.1.3 Activists -- 2.2.1.4 Businesses and IT Industry -- 2.2.1.5 Law Enforcement Agencies -- 2.2.2 Criminal Actors -- 2.2.2.1 Cybercriminals -- 2.2.2.2 Hacktivists -- 2.2.2.3 Black Hat Hackers and Virus-Hacking Tool Coders -- 2.2.2.4 State-Sponsored Attackers -- 2.2.2.5 Trade and Service Providers and Buyers -- 2.2.2.6 Insider Threat -- 2.2.2.7 Cyberterrorists -- 2.3 Concluding Remarks -- References -- Chapter 3: Terrorist Activities in the Dark and the Surface Web -- 3.1 Introduction -- 3.2 Terrorist's Activities on the Web -- 3.2.1 Propaganda -- 3.2.2 Propaganda and Social Media -- 3.2.3 Propaganda and Dark Web -- 3.2.4 Content of Propaganda -- 3.2.5 Rhetorical Structures of Terrorist Websites -- 3.2.6 Crime as a Service -- 3.2.7 Communications.